The Man’s Struggle In Dealing With Life’s Conflict as Seen in John Green’s The Fault in Our Stars - Marzona, Yessy; Yusnianti Bago, Dessy (Jurnal Ilmiah Langue and Parole, 2023)
The title of this research is "The Man's Struggle in Dealing With Life's Conflict As Seen in John Green's The Fault In Our Stars". The problem of this research is focused on the problems of internal and external conflicts experienced by woman and man as the main characters. The purpose of this research is to find out the struggles of woman and man as the main characters in dealing with life conflicts described in the novel The Fault in Our Stars by John Green. This research is descriptive qualitative research. The technique used in this research is literature to obtain certain data by searching and collecting several books related to conflict analysis in literature, by quoting sentences or words that indicate conflict, and then describing them. In the main character conflict, there are two characters who are considered as the main characters because they dominate the whole story, they are Hazel and Augustus. The research uses the theory of conflict by Wallek and Warren (1956). Conflict into two parts, namely external conflict and internal conflict. Conflict with other characters in a story or conflict with social environment which is called external conflict. While the conflict that occurs in the heart and mind, in the soul of a character or character in a story is called internal conflict. The results of this research indicate that the development of the main character in the novel is influenced by situations, people, and feelings. At first, Hazel is a girl who likes to be alone, spending her time only at home, reading books and watching tv. She then becomes a girl who wants to share with others and have friends. Augustus at first is a boy who thinks and tries to handle everything on his own, he does not want to be pitied, eventually he realizes that he needs other people in his life and is grateful for what others do to him.